2021
DOI: 10.18046/j.estger.2021.159.4412
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 y causalidad en la volatilidad del mercado accionario chileno

Abstract: En esta investigación se estudió la causalidad en el sentido unidireccional de Granger, desde el índice Infectious Disease Equity Market Volatility Tracker hacia la volatilidad del mercado accionario chileno, la cual se modela por un procedimiento autorregresivo condicional. Se aplican tres pruebas de causalidad y, de manera complementaria, la prueba de bicorrelación cruzada. Los resultados indican que este índice causa la volatilidad del mercado con la mayoría de las pruebas aplicadas. Esto señala la potencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
3
0
1
Order By: Relevance
“…For its part, the EMV-ID has a low correlation with the SP in the first days or up to a month later. These results are consistent with [ 13 , 14 , 15 , 16 ] regarding the correlation between the EMV-ID and the SP.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For its part, the EMV-ID has a low correlation with the SP in the first days or up to a month later. These results are consistent with [ 13 , 14 , 15 , 16 ] regarding the correlation between the EMV-ID and the SP.…”
Section: Resultssupporting
confidence: 91%
“…Different studies have tried to understand the volatility of financial markets and have related it to other economic, financial, and other types of variables during the pandemic [ 9 , 10 , 11 ]. Additionally, some studies have analyzed the relationship between COVID-19 news, like the Infectious Disease Equity Market Volatility Tracker (EMV-ID) series [ 12 ] and different economic and financial variables [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they find that both good and bad news are significant, however, bad news has a greater impact on volatility. Likewise, Romero-Meza et al (12) studied the causality of news about COVID-19 and the volatility of the Ipsa stock index in Chile, where they found that news about COVID-19 causes volatility in the linear and non-linear Granger sense.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…(10), Romero-Meza(12), Ashraf(13), Al-Awadhi et al (14), Reimer et al(15), who use COVID-19 infections and deaths as an important variable in stock market price volatility using univariate and causal methods.doi: 10.25100/iyc.v26i1.12930 Causality and volatility in the Colcap index of the Colombian Stock Exchange as a result of Covid-19 infections and deaths…”
mentioning
confidence: 99%
“…El mercado de valores se caracteriza por ser el ámbito de negociación pública de títulos de renta fija y variable, permitiendo la generación de información a través de los precios de los títulos. En particular, es importante comprender cómo se comportan el rendimiento y volatilidad de los precios ante distintos eventos, ya que esto se vincula con la gestión de riesgos, la administración de carteras de inversión y las decisiones de los hacedores de políticas públicas (Romero-Meza et al, 2021).…”
Section: Introductionunclassified